How to catch a unicorn ebook - Wallace, Adam (How to Catch., 2019)
The #1 New York Times bestseller! Try to catch one of the world's most elusive mythical creatures—the unicorn—in this enchanting picture book for kids, the perfect Easter basket stuffer! From the New York Times and USA Today bestselling How to Catch series comes a dazzling new adventure! Filled with zany traps, STEAM concepts, silly rhymes, and lots of rainbow unicorn fun, parents, educators, and young readers alike will delight in this colorful story as the How to Catch Kids are off in the zoo to catch this fantastical beast. Perfect for children ages 4-10, this is the ultimate unicorn gift of the year, great for birthdays, bedtime, or any occasion! Can you catch the unicorn? You'll have to use your brain, So set your traps and prep your team to pet that rainbow mane! Also in the How to Catch Series: How to Catch a Mermaid How to Catch a Dinosaur How to Catch the Tooth Fairy How to Catch a Monster and more!